Handover is guaranteed - Faye, Mamadou (Technical Centre for Agricultural and Rural Cooperation, 1998)
Mamadou Faye, of the Eaux et Forêts (Forestry department) in Mbacké, Senegal, writes about the results of close collaboration between the NGO SOS Sahel, government services and local villagers. 'The area where we live is wooded savannah, now...